Biomarkers of increased intraventricular pressure: are we ready?. (1st August 2018) - Hollinger, Alexa; Cerlinskaite, Kamile; Bastian, Kathleen; Mebazaa, Alexandre
Abstract: Natriuretic peptides (NPs) have been discovered and introduced as biomarkers in heart failure decades ago. Their limitations have led to the investigation of a number of novel biomarkers of congestion of cardiac origin thereafter. The objective of this overview was to update current evidence on cardiac and systemic biomarkers of congestion. Literature search was performed on past and current evidence of biomarkers of congestion with primary focus on NPs as the gold standard. There are various novel biomarkers of cardiac and systemic venous congestion, including CD146, adrenomedullin, and CA125, together with liver and kidney parameters that provide valuable information. Biomarkers of systemic congestion are as important as biomarkers of congestion of cardiac origin, especially in severely decompensated patients.